Geographical Analysis of Folk Songs in the Region of Çanakkale within the Frame of Human-Space Interaction - Yaşar, Okan; Yaşar, Funda Örge (Journal of History Culture and Art Research, 2023)
This study aims to analyze the reflection of physical and human geography elements in the lyrics of Turkish folk songs by making a geographical analysis of the folk songs, comprising the oral cultural heritage elements of the Çanakkale region, within the framework of human-space interaction. In the research, the document analysis method, which is one of the qualitative research methods, was used. Local folk songs were evaluated with content analysis within the framework of the specified purpose. The geographical location of Çanakkale province, its deep-rooted history of settlement and its cultural richness have affected the music culture of the region. The music culture of the region is almost the synthesis field of Western Anatolian and Thrace-Rumelian melodies. In this regard, Çanakkale region can be considered as a fusion area of North Aegean, Thrace and Southern Marmara cultural aspects. Various factors are effective in the formation of a strong folk song tradition in the Çanakkale region. An attracting part of these factors is in the field of interest of music geography, constituting a sub-branch of cultural geography. These factors consist of motifs related to location, venue and place names, landforms, hydrographic characteristics, economic activities (agriculture, animal husbandry and fishing), population movements and transportation. Çanakkale region folk songs attract attention with their successful processing of local cultural motifs and themes. Besides, the physical, human and economic geographical elements in the lyrics of the folk songs belonging to the Çanakkale region reveal that the region’s geography has been successfully analyzed. It was determined that some of the geographical elements in the local folk songs are not related to the content of the folk song, but that they are expressions that are dependent on the tradition of singing.